Hutang Luar Negeri Swasta Indonesia: Permasalahan dan Alternatif Penanganannya - Prapti, Endang Sih (Unisia, 2016)
Initially, private foreign debt is an ordinary case happening in various countries. Private institutions try to find foreign debt because of the lack of the internal fund. Both debtors and creditors would get huge economic benefits, as the relation between them can be meant as mutualistic relation. The problem would arise when one or more of three aspects appear; default, rescheduling, or repudiation. The suggested solutions are adjustmentprogram under the IMFsupport, searching for the new debt sources (at moderate rate), finding other financial aid rather than debt.